Narrative Style of Time of Habiburrahman El Shirazy in Building the Bidadari Bermata Bening Novel - Noermanza; Syafryadin; Sari, Ira Komala; Juwati; Martina , Feny (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to describe the narrative style of time of Habiburrahman El Shirazy’s in developing the Bidadari Bermata Bening novel. The research method used is the narrative method. Data collection techniques using documentation techniques. Data analysis techniques with steps: compiling a series of events in the novel, determining the time of events in the novel and the actual time of events, and determining the type of time contained in the novel. Test the validity of the data using member checking, bending, and validation of literary experts. The results showed that the narrative style of time by Habiburrahman El Shirazy in constructing the Bidadari Bermata Bening novel consists of: (1) the actual duration of the story is 59 years starting from the introduction of Ayna’s parents, until Ayna lived happily in Amman with her husband, Afif. (2) Order of the story in the novel’s text is a 10-year story of the event starting from the atmosphere of Ayna in Kanzul Ulum Islamic Boarding School, Magelang, Ayna who was still in high school class, then made a flashback or flashback, namely telling the present and past when the death event Ayna’s parents, and the Ayna parents meeting in Jordan, then the story ends with Ayna’s happiness in Amman with her husband, Afif. Then, (3) frequency in the form of repetitive frequency is more dominant followed by singular, multiple-singular, and iterative frequencies. While the events that often arise are the events of Ayna’s adolescence, namely the story of Ayna who received the National Examination score, Ayna who could not watch the Wayang Kulit performance, the love story of Ayna and Afif, the event of Ayna’s adult life which is the story of Ayna’s life with Yoyok, the difficulties of Ayna’s life after getting divorced from Yoyok, and Ayna’s success.